2018
DOI: 10.1177/0049475518788467
|View full text |Cite
|
Sign up to set email alerts
|

Human brucellosis: Experience from a tertiary care hospital in southern India

Abstract: The aim of our study was to examine and compare the clinical presentations, complications, laboratory findings, treatment and outcome of patients with acute, subacute and chronic forms of brucellosis in a tertiary care setting. This hospital-based observational study was undertaken between April 2015 and March 2017. Patients diagnosed with brucellosis, either by blood culture and/or serology, were recruited. A total of 94 cases of brucellosis of acute, subacute and chronic forms were observed in 78.7%, 15.9% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The general trend of temporal variations in Tongliao during 2007–2011 showed an increase over time, especially in counties located in the north-western regions, which was similar in neighbouring cities such as Shilingol, Chifeng and Hinggan in Inner Mongolia 6 9 14. The increase in cases could be attributed to the rapid development of livestock trading, especially goat and sheep breeding during this period,8 15 as more than 90% of human brucellosis in China was transmitted from infected goat and sheep directly or indirectly 16–18. Whereas, from the historical variations perspective, the increase of accessibility sanitation facilities, as well as the development of diagnostic and reporting networks since 2003, might be partly responsible for the visual increase of human brucellosis during 2007-2011 9 19…”
Section: Discussionmentioning
confidence: 90%
“…The general trend of temporal variations in Tongliao during 2007–2011 showed an increase over time, especially in counties located in the north-western regions, which was similar in neighbouring cities such as Shilingol, Chifeng and Hinggan in Inner Mongolia 6 9 14. The increase in cases could be attributed to the rapid development of livestock trading, especially goat and sheep breeding during this period,8 15 as more than 90% of human brucellosis in China was transmitted from infected goat and sheep directly or indirectly 16–18. Whereas, from the historical variations perspective, the increase of accessibility sanitation facilities, as well as the development of diagnostic and reporting networks since 2003, might be partly responsible for the visual increase of human brucellosis during 2007-2011 9 19…”
Section: Discussionmentioning
confidence: 90%
“…Using BLCM, we observed that the real-time PCR and LAMP assay showed diagnostic superiority over conventional microbiological culture techniques. These findings highlight the utility of LAMP and real-time PCR assays for diagnosis of brucellosis in settings, such as ours, where patients commonly present with focalized infections and/or complications of the osteoarticular and central nervous system (Patra et al 2018). Several DNA-based molecular techniques targeting the amplification of genes encoding the 31-kDa cell surface protein (bcsp31), outer membrane protein (omp2) and the 16-23S ribosomal RNA interspace region (ITS), 16S rRNA and BaSS, from clinical specimens were reported previously with varying sensitivities and specificities (Baily et al 1992;Navarro et al 2004;Imaoka et al 2007;Keid et al 2010).…”
Section: Discussionmentioning
confidence: 75%
“…These findings highlight the utility of LAMP and real‐time PCR assays for diagnosis of brucellosis in settings, such as ours, where patients commonly present with focalized infections and/or complications of the osteoarticular and central nervous system (Patra et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations